Karakteristik Petani Milenial pada Kawasan Sentra Padi di Jawa Barat - Yoyon Haryanto; Lukman Effendy; Detia Tri Yunandar (Jurnal Penyuluhan, 2022)
The presence of millennial farmers provides an alternative in accelerating the regeneration of farmers. Millennial farmers are considered capable of bridging young farmers with farmers who have been farming for a long time. However, the trend in the field has not seen the specific character possessed by millennial farmers. The purpose of this study was to described the main characteristics of millennial farmers and analyzed the factors that influence the character formation of millennial farmers. The study used a survey design with cluster random sampling technique, obtained 63 respondents representing millennial farmers in the rice center zone in three districts in West Java. Data processing used descriptive techniques and Partial Least Square The results of the study showed that the character of millennial farmers has individual characteristics in general with a relatively high level of education and has quite good business experience. The technical competence of millennial farmers that stands out is in the ability to choose commodities based on the planting calendar, market demand, land fertility and land typology, while managerial competence that is lacking from millennial farmers is in terms of the ability to manage conflicts that can occur in their business development, while social competence as a social capital strength of millennial farmers is still weak.